Association of particulate matter (PM) with respiratory symptoms among children in selected primary schools in Pahang - Zahaba, Maryam; Abdul Hadi, Hazrin; A., Hizrri; A., Norhidayah; Samsuddin, Niza; Mohd. Aris, Mohd Shukri (Zibeline International Publishing, 2018)
Particulate matter (PM) is one of the primary pollutants found in the indoor environment. It can cause deterioration of the indoor air quality (IAQ) and is often linked with adverse health effects especially towards susceptible subgroup of the population like children. School children are exposed to PM inside the classroom, as this indoor PM may originate from both indoor and outdoor sources. Furthermore, ambient surrounding could be one of the major factors that contribute to its high concentration, specifically for school environment like government-subsidized schools in Malaysia whereby the schools are using natural ventilation systems to control the thermal comfort inside the classrooms. Hence the infiltration of outdoor PM into the indoor is probably high and significant. The high concentration of PM may affect the children’s health and learning performances. Due to this reason, it is important to study the effects of PM towards children. Thus, this study aims to assess the concentrations of PM and selected IAQ parameters in the school indoor environment with distinct background characteristics including residential, industrial, and rural areas. PM and IAQ parameters (temperature, relative humidity (RH), carbon monoxide (CO) and carbon dioxide (CO2)) were assessed for 8-hours duration via DustMate Environmental Dust Detector (Turnkey Instruments, USA) and VelociCalc® Multi-Function Ventilation Meter 9565 (TSI®, USA) respectively, during occupied and non-occupied time in the classrooms. Second, considering the children’s prolonged and repetitive exposure towards PM in school indoor environment and their body sensitivity, this study also screened for the prevalence of non-specific respiratory disease (NSRD) and persistent cough and phlegm (PCP) among children via structured questionnaire developed by American Thoracic Society’s Division of Lung Diseases (ATS-DLD-78-C). Higher concentrations of PM and prevalence of respiratory symptoms in the school from the industrial area were expected, due to the high concentration of PM originated from nearby industrial activities and anthropogenic sources. Hopefully, better understanding and insights on the issue were obtained through this study.